Pengaruh Pemberian Pupuk Kotoran Kambing Terhadap Pertumbuhan dan Hasil Tanaman Bayam Merah (Amaranthus tricolor L.) - Komang Dean Ananda; I Gusti Ayu Diah Yuniti; Cokorda Javandira; Antonius Talu (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2024)
Red spinach (Amaranthus tricolor L.) is a plant that has high economic value compared to several other types of spinach. This can be seen from the high demand for this vegetable in several supermarkets, hotels and restaurants. Based on the climatological aspect, the Indonesian region is very suitable for red spinach cultivation. The purpose of this study was to determine the effect of the type of planting media on the growth and yield of red spinach plants and to determine which plant media provided the best growth and yield of red spinach plants. This study used randomized block design (RBD) research method using various kinds of organic fertilizers, namely goat manure with 6 levels K0 (without fertilizer), K1 (10 g goat manure/10 kg of soil), K2 (20 g goat manure)/10 kg of soil), K3 (30 g of goat manure/10 kg of soil), K4 (40 g of goat manure/10 kg of soil), and K5 (50 g of goat manure/10 kg of soil). Plant height, number of leaves, root length, leaf area, total fresh weight of plants, total dry weight of plants The results of goat manure application had a very significant effect on plant height, number of leaves, leaf area, root length, total fresh weight of plants, weight total crop oven dry The application of goat manure 8 to / ha and 10 / ha gave the best results on total plant fresh weight of 22.17 g and 26.245 g total crop oven dry weight of 4.322 g and 5.342 g